The arts of encounter : Christians, Muslims, and the power of images in early modern Spain - Infante, Catherine (Toronto Iberic., 2022)
"Images of crosses, the Virgin Mary, and Christ, among other devotional objects, pervaded nearly every aspect of public and private life in early modern Spain, but they were also a point of contention between Christian and Muslim cultures. Writers of narrative fiction, theatre, and poetry were attuned to these debates, and religious imagery played an important role in how early modern writers chose to portray relations between Christians and Muslims. Drawing on a wide variety of literary genres as well as other textual and visual sources, including historical chronicles, travel memoirs, captives' testimonies, and paintings, Catherine Infante traces the references to religious visual culture and the responses they incited in cross-confessional negotiations. She reveals some of the anxieties about what it meant to belong to different ethnic or religious communities and how these communities interacted with each other within the fluid boundaries of the Mediterranean world. Focusing on the religious image as a point of contact between individuals of diverse beliefs and practices, The Arts of Encounter presents an original and necessary perspective on how Christian-Muslim relations were perceived and conveyed in print."--